Following Papa's song - Marino, Gianna (New York : Viking, an imprint of Penguin Group (USA), 2014)
"Little Blue, a young humpback whale, has never made the long migration up the coast, and he is worried about his first long journey with Papa"--
Keywords: Humpback whale -- Fiction; Whales -- Fiction; Animals -- Migration -- Fiction; Father and child -- Fiction